[Ekslibris] Alan D. M. Wambeek / J. B. - Battermann, Johannes (1909-1999) ([wydawca nieznany], 1958)
Na tle obfitych labrów tarcza z herbem, u dołu na szarfie napis: Alan D. M. Wambeek. Sygnatura artysty w obrębie kompozycji.